Thin-film optoacoustic transducers for the subcellular Brillouin oscillation imaging of individual biological cells - Perez-Cota, Fernando; Smith, Richard J.; Moradi, Emilia; Marques, Leonel; Webb, Kevin F.; Clark, Matt (Optical Society of America, 2015)
Mechanical characterisation and imaging of biological tissue has piqued interest in the applicability to cell and tissue biology. One method, based on detection of Brillouin oscillations, has already lead to demonstrations on biological cells using ultrasound in the GHz range. In this paper we present a technique to extend this picosecond laser ultrasound technique from point measurements and line scans into high resolution acoustic imaging. Our technique uses a three layered metal-dielectric-metal film under the cell as a transducer for the generation of ultrasound. The design of this transducer and measuring system is optimised to address a limiting SNR factor related to the cell fragility; its sensitivity to laser light. Our approach shields the cell from laser radiation while having acoustic generation, optical detection and aiding heat dissipation. For that, Brillouin detection is performed in transmission rather than reflection. The conditions necessary to perform successfully this kind of detection are discussed and experimental results on phantom, fixed and living cells are presented.